The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1097/00005537-200301000-00022
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Nasal Polyposis by Immunoglobulin E and Interleukin‐5 Is Completed by Transforming Growth Factor‐β1

Abstract: High tissue TGF-beta1 quantity in healthy nasal mucosa without its active form on the cell surface and its low quantity in polyps may reflect its essential role in the inhibitory mechanisms of nasal polyposis. Interleukin-5 plays a key role in the eosinophil recruitment and activation, and both atopic and nonatopic pathways might activate this process. The main sources of IL-5 and TGF-beta1 are the eosinophils and macrophages. Immediate hypersensitivity, besides other mechanisms, might be related to atopic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 25 publications
1
36
0
5
Order By: Relevance
“…Both latency-associated peptide (LAP) and latent TGF-β-binding protein (LTBP-1) play an important role in the regulation of TGF-β1 by preventing it from exerting its biological functions [9,10]. This repression is important for maintaining normal mucosal structure, as evidenced by the presence of only a few active TGF-β1 proteins but a substantial amount of nonactive protein in healthy mucosa [11]. However, a significant increase in the active form can be detected in patients with CRS, indicating that the activation of TGF-β1 is out of control and is involved in the tissue remodeling process of CRS [12].…”
Section: The Dysregulated Activation Of Tgf-β1mentioning
confidence: 99%
“…Both latency-associated peptide (LAP) and latent TGF-β-binding protein (LTBP-1) play an important role in the regulation of TGF-β1 by preventing it from exerting its biological functions [9,10]. This repression is important for maintaining normal mucosal structure, as evidenced by the presence of only a few active TGF-β1 proteins but a substantial amount of nonactive protein in healthy mucosa [11]. However, a significant increase in the active form can be detected in patients with CRS, indicating that the activation of TGF-β1 is out of control and is involved in the tissue remodeling process of CRS [12].…”
Section: The Dysregulated Activation Of Tgf-β1mentioning
confidence: 99%
“…Eosinophils are sources of interleukins that bear autocrine and modulator effect on the function of other cells 14 . The continuity of the inflammatory response seen in the eosinophylic NSP is related to cytokines such as IL5 and GM-CSF which increase survival and reduce the eosinophil apoptosis rate 7,8,[10][11][12] . Therefore, they regulate proliferation and cell ac- tivation, broadening local immune response and polyp formation.…”
Section: Discussionmentioning
confidence: 99%
“…They also bear morphologic alterations such as nasal membrane hyperplasia, irregularity of gland distribution, squamous metaplasia and edema ( Figure 2) 3,4 . Although it has been related to IgE mediated hypersensitivity, or nasal allergy, studies have shown that allergy is only one possible cause or a contributing factor [5][6][7] . Eosinophil and polyp structural cells secrete cytokines that maintain the inflammation process and the Eosinophil build up constant.…”
Section: Introductionmentioning
confidence: 99%
“…and chemokines (eotaxin, RANTES) are involved in this process. IL-5, an important factor in eosinophilic inflammation, is higher in nasal polyp than in healthy mucosa [2,3].…”
Section: Introductionmentioning
confidence: 97%